Bentuk dan Efektivitas Dakwah di TVRI Kalimantan Timur - Syobah, Sy. Nurul (FENOMENA, 2015)
Television is a technology product which becomes the need of human being. It becomes an important part of human life from morning up to the next morning. It is important, since it becomes an effective media to promote education, information, entertainment, and social connection. This is a descriptive qualitative research with communicative and management approach which aims at describing the effectiveness of daâwah in TVRI Kalimantan Timur. The findings of the study shows that there are two kinds of daâwah in TVRI, they are: 1) integrative daâwah which consists of the daâwah in the daâwah and non-daâwah program, 2) partial daâwah which is done by daâwah in the process of production and in the process of broadcasting. To measure the effectiveness of daâwah, it was done by doing a survei to the TVRI viewers. The result shows that daâwah in TVRI is not effective yet, since it has some flaws and weaknesses. Most of viewers state that the program should be improved by developing the quality of daâwah program in TVRI. TVRI has done and tried hard to create the program, yet it still needs to be improved and produce a qualified daâwah program.